Species of the Genus Crotalaria L. and Their Biological Significance - Berdiqulov Xudoyshukur Keldiyorovich (Web of Journals Publishing, 2023)
In this article, scientific information is given about the species of Crotalaria L. genus and their biological importance, their distribution and cultivation status in the regions, their importance in industry and pharmaceutics, and agriculture. In this article, it is scientifically justified to increase the fertility of barren lands through the cultivation of Crotalaria L. species.